Validation of a novel imaging-guided and anatomy-based classification system for anorectal fistulas: a retrospective clinical evaluation study - Antonio Brillantino; Francesca Iacobellis; Luigi Marano; Adolfo Renzi; Pasquale Talento; Luigi Brusciano; Claudio Gambardella; Umberto Favetta; Michele Schiano Di Visconte; Luigi Monaco; Maurizio Grillo; Mauro Natale Maglio; et al. (Annals of Coloproctology)
Purpose This study was conducted to evaluate the validity of a new imaging-guided, anatomy-based classification of anorectal fistulas in defining disease severity and predicting surgical outcomes. Methods This multicenter, retrospective cohort study analyzed data from patients with perianal fistulas who underwent surgery between 2017 and 2023. All patients underwent preoperative 3-dimensional endoanal ultrasound, with adjunctive magnetic resonance imaging performed if ultrasound indicated a complex fistula. Imaging examinations were retrospectively evaluated to categorize fistulas according to the Garg classification and the newly proposed classification system. The new classification included 6 severity grades based on the characteristics of the primary tract: submucosal, intersphincteric, low transsphincteric, high transsphincteric, multiple, and suprasphincteric/extrasphincteric. Each grade was further subdivided into 3 subtypes (A, B, C) based on the extension of secondary tracts. Results When compared with the new classification, the Garg classification demonstrated a slightly lower ability to predict the feasibility of fistulotomy in simple fistulas (94.2% vs 99.1%; Fisher exact test, P=0.006). A strong positive correlation was found between the surgery failure rate and the severity grade of the new classification (Spearman rho, 0.90; P<0.001), whereas the Garg classification showed a nonsignificant positive correlation with surgical failure rate (Spearman rho, 0.90; P=0.08). Conclusion The new imaging-guided, anatomy-based classification of anorectal fistulas demonstrates high accuracy in defining disease severity. It represents a valuable tool for preoperative grading of anal fistulas, standardizing the reporting of diagnostic imaging, and improving the communication of findings among healthcare professionals.